Enhancing Learning Disability Identification in Saudi Arabia: (A Qualitative Study) - Hassan Alwadei (Journal of Arts, Literature, Humanities and Social Sciences, 2025)
Instructional coaches play a crucial role in supporting teachers with the referral and evaluation processes for identifying students with learning disabilities (LD) in Saudi Arabia. They also assist students in navigating daily learning and assessment activities. This study examined the perspectives of instructional coaches regarding the current LD identification model, its effectiveness, and the feasibility of implementing Multi-Tiered Systems of Support (MTSS) as an alternative framework. Through semi-structured interviews with 12 instructional coaches, the study evaluated the strengths and limitations of Saudi Arabia’s existing identification practices. The findings revealed significant concerns regarding the accuracy of current methods and the risks associated with misidentifying students. While MTSS is not yet utilized in Saudi schools, the results suggest it could offer a more comprehensive and reliable approach to addressing students’ academic and behavioral needs. The study emphasizes the importance of culturally and linguistically appropriate practices and advocates for the phased implementation of MTSS, supported by robust teacher training programs. This study contributes to a deeper understanding of LD identification challenges in Saudi Arabia and highlights the potential of MTSS to improve outcomes, offering practical recommendations for policy and future research.